The Effect of Combination of Meniran (Phyllanthus niruri), Moringa (Moringa oliefera) and Surgery (Curcuma domestica) Extracts on Total Leukocytes and Differential Leukocyte of Broiler Chicken - Puji Astuti; Heru Suripta (Bantara Journal of Animal Science, 2022)
This study aims to determine the effect of the combination of Phyllanthus niruri, moringa and turmeric extract on total leucocytes and defferential leucocyte of broiler chickens. The study was conducted in March - May 2021. The research used 60 broiler chickens with an initial weight of 41.48 ± 0.99 g. The feed given was commercial feed containing 22% protein. The study used a completely randomized design (CRD) with 4 treatments and 3 replications, each of which consisted of 5 DOCs. The treatments consisted of T0 (100% water), T1 (50% Phyllanthus niruri+ 25% moringa + 25% turmeric), T2 (25% Phyllanthus + 50% Moringa + 25% turmeric), T3 (25% Phyllanthus + 25% Moringa + 50% turmeric. The observed variables were total leucocytes and differential leucocytes (lymphocytes and heterophils). The results showed that the combination of Phyllanthus, moringa and turmeric extract increased the number of leucocytes, the percentage of lymphocytes and decreased the percentage of heterophils. but still within normal limits. The results showed that the combination of Phyllanthus extract, moringa and turmeric increased the number of leucocytes, the percentage of lymphocytes and decreased the percentage of heterophils. but still within normal limits.